Function Consuming sebagai Tingkat Kecakapan Literasi Media Digital Masyarakat Yogyakarta - Ade Irma Sukmawati; Irma Handayani (Program Studi Ilmu Komunikasi, 2022)
Digital competence is one of the skills for users in using digital media. Research on mapping the digital competence category of the people of Yogyakarta was carried out to know the media digital positioning competence of digital media users. The position of digital media user skills is categorized by the k-NN (k Nearest Neighbor) technique data mining method. The objective of this research using the k-NN technique data mining method was carried out by compiling categories that refer to attributions where the attribution refers to the ten competencies of Japelidi's digital media users. The digital media user skills category has four quadrants: Function Consuming, Function Prosuming, Critical Consuming, and Critical Prosuming. This research was conducted in Yogyakarta from June-July 2020 because, during this period, there was a surge in digital media users due to the pandemic. The findings in this research provide information that the competence of using digital media for Yogyakarta residents in the period of June-July 2020 is in the Function Consuming section, and it is in the first quadrant